2009
DOI: 10.1038/jhg.2009.87
|View full text |Cite
|
Sign up to set email alerts
|

Validation of eight genetic risk factors in East Asian populations replicated the association of BRAP with coronary artery disease

Abstract: Coronary artery disease (CAD) is caused by a thrombotic occlusion or spasm of the coronary artery. Association of genetic variants with susceptibility to CAD has been reported in various populations, but the association should be replicated in other populations to establish the role of genetic variants in CAD. We conducted a case-control study with a total of 1480 CAD cases and 2115 controls from two East Asian populations, Japanese and Korean, to validate the associations of CAD with eight single nucleotide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…The minor G allele of SNP rs11066001 was demonstrated to cause a higher BRAP expression level than the common A allele 2) . The findings were further replicated by an independent study using Japanese and Korean populations 3) . In addition, our group showed an association between SNP rs11066001 and carotid atherosclerosis (unpublished data) and coronary stenosis (unpublished data).…”
supporting
confidence: 68%
“…The minor G allele of SNP rs11066001 was demonstrated to cause a higher BRAP expression level than the common A allele 2) . The findings were further replicated by an independent study using Japanese and Korean populations 3) . In addition, our group showed an association between SNP rs11066001 and carotid atherosclerosis (unpublished data) and coronary stenosis (unpublished data).…”
supporting
confidence: 68%
“…Several large-scale association studies including GWAS studies have identified several loci associated with the risk of CAD and MI [2,3,5,6,7,9,10,14,15,16,17,18,19,20]. However, not all of the identified associations could be replicated in other studies.…”
Section: Discussionmentioning
confidence: 62%
“…However, not all of the identified associations could be replicated in other studies. Kunihiko et al [20] validated 8 genetic risk factors in East-Asian populations (Japanese and Korean, a case-control study with a total of 1,480 CAD cases and 2,115 controls) and only one SNP in BRAP (rs11066001) showed a significant association with CAD. Failure to replicate the association with other SNPs reported in European populations might suggest that their contributions to CAD were not large enough in European populations.…”
Section: Discussionmentioning
confidence: 99%
“…Of note is that rs11066001 is in LD with rs3782886, with R 2 of 0.891 and D` of 1 in our data. Some studies reported that two SNPs—rs11066001 and rs3782886—in BRAP were significantly associated with coronary artery disease in Asian populations [14], [35], and metabolic syndrome in the Han Chinese population [36]. Another study reported the association of rs11066001 with carotid atherosclerosis in Taiwanese [15].…”
Section: Discussionmentioning
confidence: 99%